Penguatan Literasi Dasar Berbasis Sastra Anak bagi Siswa Sekolah Dasar - Kartikasari H.S., Apri; Marlina, Diyan; Ardiana, Linda Yusli Exsa (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this community service activity is to provide socialization and assistance to students at the elementary school level in strengthening basic literacy. The material used to strengthen children's literacy skills is by introducing children's literature from various genres such as rhymes, poems, and fairy tales (fables and legends). This activity was carried out at SDN Gayam 2, Kendal District, Ngawi Regency with the subject of 28 students. This activity was carried out by socialization method by showing two short films about the importance of basic literacy and delivering short material on literacy, as well as direct assistance to grade 1-6 students by introducing basic literacy based on children's literature. The enthusiasm of the students is so great because this activity is carried out in a fun way. Based on the results of the service, it is known that of the 28 students who participated in this activity, four students were not very literate, and one student could not read and write at all. This activity is important to assist teachers in providing assistance in strengthening basic literacy to students as a provision for strengthening technical or advanced literacy.